Implementation of the Independent Curriculum in Islamic Religious Education Learning: a Comparative Study of Madrasah Aliyah at Palu City - Sabriyah Aziz; Askar Askar; Ubadah Ubadah; Muhammad Munif (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2026)
This study examines the planning, implementation, and enabling and constraining factors of the Merdeka Curriculum in Islamic Religious Education at two state Islamic senior high schools in Palu. Using a qualitative comparative case study, data were collected through in-depth interviews, classroom observations, and document analysis involving principals, curriculum vice principals, and teachers directly engaged in curriculum implementation. Data were analyzed thematically through data condensation, data display, and conclusion drawing and verification, while trustworthiness was ensured through triangulation and member checking. The findings show that both schools have formally responded to the curriculum through instructional planning and classroom adjustment, but the depth of implementation differs. State Islamic Senior High School 1 Palu is more adaptive in contextualizing teaching documents and adopting innovative learning practices, whereas State Islamic Senior High School 2 Palu is more cautious, particularly in topics requiring accurate transmission of religious knowledge. Implementation is supported by school leadership and teacher collaboration, but constrained by limited infrastructure, administrative burden, and inadequate learning resources. The study concludes that curriculum implementation in Islamic Religious Education is shaped not only by policy adoption but also by institutional adaptive capacity, teacher readiness, and local school context.